2016
DOI: 10.1210/jc.2015-3095
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated With Low NAD+/SIRT Pathway Expression in Adipose Tissue of BMI-Discordant Monozygotic Twins

Abstract: Our data highlight a strong relationship of reduced NAD(+)/SIRT pathway expression with acquired obesity, inflammation, insulin resistance, and impaired mitochondrial protein homeostasis in SAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
138
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 39 publications
10
138
1
Order By: Relevance
“…It is also possible that the alterations in circulating extracellular NAMPT (eNAMPT) affects neuronal metabolic signals associated with hypothalamus, and is involved in the pathogenesis of systemic metabolic complications observed in ANKO mice (Imai and Yoshino, 2013; Yoon et al, 2015). Given previous findings demonstrating that reduction in adipose NAMPT expression and NAD + content is associated with obesity and its metabolic complications in people and rodents (Ando et al, 2005; Jukarainen et al, 2015; Kovacikova et al, 2008; Mercader et al, 2008; Xu et al, 2012; Yoshino et al, 2011), our data strongly suggest that impaired NAMPT-mediated NAD + biosynthesis in adipose tissue plays a causative role in the pathophysiology of obesity-associated metabolic derangements, and thereby could be an important therapeutic target. Indeed, recent studies have shown that systemic administration of NAD + intermediates, such as NMN and NR, improves insulin resistance, dyslipidemia, NAFLD, and glucose intolerance, in obese mice (Canto et al, 2012; Canto et al, 2015; Gariani et al, 2015; Imai and Yoshino, 2013; Yoshino et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is also possible that the alterations in circulating extracellular NAMPT (eNAMPT) affects neuronal metabolic signals associated with hypothalamus, and is involved in the pathogenesis of systemic metabolic complications observed in ANKO mice (Imai and Yoshino, 2013; Yoon et al, 2015). Given previous findings demonstrating that reduction in adipose NAMPT expression and NAD + content is associated with obesity and its metabolic complications in people and rodents (Ando et al, 2005; Jukarainen et al, 2015; Kovacikova et al, 2008; Mercader et al, 2008; Xu et al, 2012; Yoshino et al, 2011), our data strongly suggest that impaired NAMPT-mediated NAD + biosynthesis in adipose tissue plays a causative role in the pathophysiology of obesity-associated metabolic derangements, and thereby could be an important therapeutic target. Indeed, recent studies have shown that systemic administration of NAD + intermediates, such as NMN and NR, improves insulin resistance, dyslipidemia, NAFLD, and glucose intolerance, in obese mice (Canto et al, 2012; Canto et al, 2015; Gariani et al, 2015; Imai and Yoshino, 2013; Yoshino et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…Aging, which is another major risk factor of metabolic complications, also impairs NAMPT-mediated NAD + biosynthesis in adipose tissue (Yoshino et al, 2011). Interestingly, data obtained from recent studies conducted in people demonstrate that the alterations in adipose NAMPT-mediated NAD + biosynthesis are associated with obesity and its metabolic complications (Jukarainen et al, 2015; Kovacikova et al, 2008; Varma et al, 2007; Xu et al, 2012). For example, adipose tissue NAMPT protein content or NAMPT gene expression is decreased in subjects who are insulin-resistant, compared to body mass index matched insulin-sensitive counterparts (Varma et al, 2007; Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…5B), thus confirming a critical role of MAPK activation in high-glucose induction of RTA expression. To investigate other mechanisms that might be involved in high-glucose induction of KSHV lytic replication, we examined the expression of SIRT1, which is a member of the class III HDACs and a key factor involved in the development of diabetes (34)(35)(36)(37)(38)(39)(40). In addition, several previous studies demonstrated the involvement of SIRT1 in the regulation of KSHV lytic gene expression through epigenetic remodeling (41)(42)(43).…”
Section: Methodsmentioning
confidence: 99%
“…PPARGC1A is a transcriptional coactivator that modulates the genes involved in energy metabolism, being a central regulator of mitochondria biogenesis [24][25][26][27]. SIRT1, which is another important mediator of mitochondrial biogenesis and energy expenditure in AT [27][28][29], is widely known as a negative regulator of cellular senescence [30,31]. In humans, increased AT SIRT1 mRNA levels and activity associates with mitochondrial function [28,29] and with reduced markers of cellular senescence [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1, which is another important mediator of mitochondrial biogenesis and energy expenditure in AT [27][28][29], is widely known as a negative regulator of cellular senescence [30,31]. In humans, increased AT SIRT1 mRNA levels and activity associates with mitochondrial function [28,29] and with reduced markers of cellular senescence [32,33]. Furthermore, DBC1 interacts and inhibits the activity of Sirt1 [34], a crucial component for the prevention of cellular senescence [35,36].…”
Section: Discussionmentioning
confidence: 99%